FRI0056 Increased expression of the collagen internalization receptor ENDO180 in fibroblast-like synoviocytes of patients with rheumatoid arthritis. (15th June 2017) - Yan, L; Wen, Y
Abstract : Background: Hyperproliferative and invasion are the characteristics of fibroblast-like synoviocytes in rheumatoid arthritis (RA-FLSs), which contribute mainly to RA disease progression and ultimately to joint destruction. Endo180 is a recycling endocytic receptor that has functions to regulate cell migration and bind and internalize collagens. However, the expression of Endo180 in RA-FLSs and its underlying mechanisms remain unclear. Objectives: To examine the expression of Endo180 in RA-FLSs and the role it played in RA. Methods: Tissues were collected from RA patients with joint replacement surgery or arthroscopy and RA-FLSs were obtained by tissue culture; Westren blot was used to measure the expression of Endo180 in RA-FLSs. Chemically synthesized small interference RNA (siRNA) specifically targeting Endo180 gene was transfected into RA-FLSs by cationic liposome; The interference efficiency of Endo180-siRNA on the production of Endo180 mRNA and protein was determined by RT-qPCR and Western blot respectly; The proliferative inhibition rate was examined by CCK8 assay and the migration of RA-FLSs were examined by Transwell assay. Results: Expression of Endo180 was obviously higher in fibroblast-like synoviocytes in RA than OA and the traumatic patients. And its expression level has positive correlation with disease activity. The proliferative inhibition rate was obviously higher in the Endo180-siRNA group than the control groups (P<0.05) after transfection for 48h (8.31%±1.17%), 72h (15.93%±2.12)%), 96h (18.01%±2.78%). Transwell migration assay demonstrated the RA-FLSs through the transwell membrane in Endo180-siRNA group (21.27±6.35) were lesser than the NC-siRNA group (80.20±11.12) (P<0.05)and the blank control group (82.17±10.36) (P<0.05). Conclusions: Endo180 may play a role in the regulation of proliferation and migration of RA-FLSs, which may provide beneficial therapeutic effects in RA. References: Melander MC, Jürgensen HJ, Madsen DH, et al. The collagen receptor uPARAP/Endo180 in tissue degradation and cancer (Review).Int J Oncol. 2015 Oct;47(4):1177–88. doi: 10.3892/ijo.2015.3120. Epub 2015 Aug 12. Madsen DH, Jurgensen HJ, Ingvarsen S, et al. Endocytic collagen degradation: a novel mechanism involved in protection against liver fibrosis. J Pathol. 2012 May;227(1):94–105. doi: 10.1002/path.3981. Epub 2012 Feb 17. Disclosure of Interest: None declared